A abolição do tráfico de escravos no Atlântico Sul: Portugal, o Brasil e a questão do contrabando de africanos - Guizelin, Gilberto Da Silva [UNESP] (Universidade Federal de São Paulo - UNIFESP, 2013)
This article deals with the issue of the abolition of the slave trade in the South Atlantic. It is important to say that this study does not deal with this discussion from the exclusive framework of the diplomatic relations between Great Britain and Brazil regarding the question of slave trade, it is also based on the traditional relations developed between Portugal and Brazil in respect to that same question in the mid-nineteenth century.

Este artigo aborda a temática da abolição do tráfico de escravos realizado no Atlântico Sul. Cumpre destacar que o estudo que aqui se apresenta não traz uma discussão a partir do enquadramento das relações diplomáticas anglo-brasileiras com a questão do tráfico de escravos, mas sim com base no condicionamento do relacionamento luso-brasileiro com esta questão em meados do século XIX.
The Abolition of the Slave Trade in the South Atlantic: Portugal, Brazil and the Issue of the Smuggling of Africans
Keywords: slave trade; slave trade diplomacy; Portugal; Brazil; tráfico escravo; diplomacia do tráfico; Portugal; Brasil